E-Procurement System In The Mechanism Of Procurement Of Goods And Services Electronically - Ariman Sitompul (International Asia Of Law and Money Laundering, 2022)
In the implementation of State Life, the government is always required to promote public welfare. Because there is no country that does not have a purpose and diverse purposes of that country. To carry out this obligation, the government has an obligation to provide the needs of the people in various forms in the form of goods, services and infrastructure development. on the other hand, the government also needs the goods and services in implementing the government, for that it is necessary to procure goods and services. Procurement of goods and services is essentially an effort by the user to obtain or realize the goods and services he wants by using certain methods and processes in order to achieve an agreement on price, time and other agreements. In order for the nature and essence of the procurement of goods and services can be carried out as well as possible, then both parties, namely the users and providers, must always be based on the philosophy of procurement of goods and services, subject to the ethics and norms of procurement of goods and services that apply, follow the principles, methods and processes of procurement of goods and services that are standard. In the system of procurement of Good Goods and services is a system of procurement of goods and services that are able to apply the principles of good governance and Clean Governance (Good Governance and Clean Governance), encourage the efficiency and effectiveness of public spending, as well as structuring the behavior of the three pillars (government, private and public).